Hyaluronidase Inhibits the Proliferation and the Viability of Cumulus Cells Through the Inhibition of Midkine - Erguven, Mine; Cetin Aktas , Esin; Irez, Tulay (Gynecology Obstetrics & Reproductive Medicine, 2025)
OBJECTIVE: Hyaluronidases (HYAse) break down hyaluronic acid, which is found in high levels in the cumulus-oocyte complex during oocyte preparation for IVF. Using HYAse, we aimed to investigate whether a growth factor, midkine (MK), has a role in the proliferation and viability of cumulus cells (CCs) during the denudation process. STUDY DESIGN: A prospective, randomized study was done with 90 females aged 21-40 undergoing ICSI from September 2017 to September 2018. CCs were cultured via a mechanical application from male factor cases at the IVF clinic of a private hospital. HYAses in concentrations of 0.1 IU/mL (The lowest concentration), 1 IU/mL, and 10 IU/mL (The highest concentration) were applied to CCs. Every 48 hours of 24 hours, cell proliferation and apoptosis indices (Flow cytometry) with MK levels (ELISA) and the ultrastructure of cumulus cells (TEM) at the 48th were evaluated. A one-way ANOVA test was used, and P<0.05 was considered statistically significant. RESULTS: All concentrations decreased the cumulus cell numbers for 48 hours. The highest decrease in cell number was detected at the highest concentration at the 48th h. In concordance with this result, the highest increase in apoptotic and dead cell rates with the lowest viable cell rate was detected at the highest concentration at the 48th h. The highest concentration led to the highest decrease in MK levels at the 48th h. CONCLUSIONS: HYAse inhibits the proliferation of CCs by inhibiting MK in a time and concentration-dependent manner.